Comparison of Bridge Dynamic Amplifications Due to Articulated 5-Axle Trucks and Large Cranes - Daniel Cantero; Arturo González; Eugene J. OBrien (The Baltic Journal of Road and Bridge Engineering)
Extremely heavy vehicles are becoming more common on European highways due to the increasing demand for transport of heavy goods. These vehicles require permits from the road authorities to travel over a specified route. The authorities must ensure the bridge infrastructure remains safe when traversed by these very heavy vehicles and an escort is typically used to reduce loading in long-span bridges. In the case of short- and medium-span bridges, the closely spaced axle’s forces of cranes form a critical traffic load configuration that must be carefully assessed before granting a permit. In this paper, the parameters of a 3D vehicle-bridge interaction model are varied using Monte Carlo simulation to find the dynamic increment in the bridge response due to large cranes. A number of bridge spans, simply supported and fixed, and road conditions (with and without a damaged joint prior to the bridge) are tested and the bridge response is compared to conventional 5-axle trucks.